2022
DOI: 10.1177/24715492211063108
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Tumor Prostheses for Primary or Revision Reverse Total Shoulder Arthroplasty With Proximal Humeral Bone Loss

Abstract: Background During shoulder arthroplasty with substantial bone and soft tissue loss, reverse shoulder arthroplasty (RSA) with a tumor prosthesis may restore function, reduce pain, and improve implant fixation. Methods Thirteen adult patients undergoing RSA using a tumor prosthesis system were retrospectively reviewed. Preoperative visual analog score (VAS), single assessment numeric evaluation (SANE), American Shoulder and Elbow Surgeons (ASES) score, simple shoulder test (SST), and forward flexion were compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…This systematic review included 9 studies. 5 , 17 , 24 , 26 , 28 , 33 , 41 , 61 , 63 The study characteristics are shown in Table I .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This systematic review included 9 studies. 5 , 17 , 24 , 26 , 28 , 33 , 41 , 61 , 63 The study characteristics are shown in Table I .…”
Section: Resultsmentioning
confidence: 99%
“…17 , 28 , 33 , 61 Seven studies did not have consecutive inclusion of patients, because of a retrospective design. 5 , 17 , 26 , 33 , 41 , 61 , 63 Two studies did not clearly report outcomes, as they did not report individual patient data. 28 , 33 Four studies did not clearly report site clinic demographic information, as no information was provided about the center or the surgeons.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations